Indonesian smallholder beef producers’ perception of sustainability and their reactions to the results of an assessment using the sustainability assessment of food and agriculture system (SAFA) – a case study based on focus group discussions - Gayatri, S.; Vaarst, M. (Journal of the Indonesian Tropical Animal Agriculture, 2020)
Beef cattle farmers were interviewed about what “sustainability” means to them with regard to their daily practices, both in their daily working life and after being confronted with the results of an assessment conducted on their farms prior to a focus group discussion (FGD) utilizing the Sustainability Assessment of Food and Agriculture (SAFA) system developed by the Food and Agriculture Organization (FAO) of the United Nations. The study presented in this article was based on two FGDs, using the results of the SAFA online assessment as a tool to initiate and facilitate the discussions. The two group discussions were recorded using a digital voice recorder, transcribed in full and then coded using the software program Transana. The discussions were organized into themes, which allowed a basis for the further analysis. The themes allowed us to build a picture of the participants’ views and thoughts on sustainability with regard to their farming management practices in the light of the SAFA framework, and their own thoughts and perception of the government’s action to promote sustainability, as well as to consider its implications for the futures of their own farms. The interviewed beef cattle farmers thought of sustainability on a day-to-day context rather than as a multi-dimensional concept. In their views, sustainability was very much about being able to continue farming, for the farm to survive and about being able to hand it over to the next generation. However, when presented with the four dimensions of the SAFA framework, they acknowledged the wider perspectives and different aspects of sustainability and reflected about how their own agricultural practices related to these wider aspects too.